The Relationship Between Social Support and Blood Pressure Control Behaviors among Pregnancy Induced Hypertension - เผือกพันธ์ , วิไลลักษณ์; พานเมือง , สิวาพร; วันชูเสริม , ปาริชาติ (Journal of Health Science of Thailand, 2026)
Nursing care of pregnancy-induced hypertension is an important matter that nurses and family members must work together to care for. This study aimed to examine the relationship between social support, personal factors and blood pressure control behaviors among pregnancy-induced hypertension at the antenatal clinic of Mahasarakham Hospital. The sample consisted of 98 participants. Data were collected using a social support questionnaire and a blood pressure control behavior questionnaire for pregnant women with pregnancy-induced hypertension, with Cronbach’s alpha coefficients of 0.87 and 0.85, respectively. The data were analyzed using frequency, percentage, mean, standard deviation, and Pearson’s correlation coefficient. The results indicated that overall social support was at a good level (mean=3.66, SD=0.68), while blood pressure control behaviors among pregnant women with pregnancyinduced hypertension were moderate (mean=2.28, SD=0.24). Blood pressure control behavior in pregnancy-induced hypertension was significantly positively associated with social support and education level (p<0.05). This shows that receiving support from family members and high-level education allows pregnancy-induced hypertension to have appropriate eating behaviors for the disease, exercise to maintain good health, and take medication to prevent complications. Therefore, prenatal clinic nurses should organize activities that are consistent or can be developed in various areas in order to encourage pregnant women to have appropriate behaviors in all aspects.